Variation of Polymer Matrix On the Quality of Bioplastic from Cassava Peel Waste from Tapai Industry in Bogor - Sholeha, Novia Amalia; Muthmainah, Nada Ghaida; Robyano, Rifky Ardiansyah; Sophia, Halida; Susanti, Indri; Ramadhania, Nurina Rizka (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Plastic waste originating from commercial sources presents significant environmental challenges, leading to the creation of biodegradable alternatives derived from renewable materials. This research investigates the feasibility of utilizing cassava peel starch (CPS), an agro-industrial by-product, as a foundational material for bioplastic manufacturing. To overcome the limitations of pure starch, such as brittleness and insufficient water resistance, a bioplastic was produced through solvent casting by combining a blend of chitosan, a natural biopolymer, and polyvinyl alcohol (PVA), a synthetic polymer, to improve its mechanical and physical properties. CPS was extracted and then analyzed for yield, moisture, and starch content. The interactions among components in bioplastics were examined utilizing FTIR and SEM techniques. FTIR analysis revealed physical interactions devoid of chemical bonding, whereas SEM demonstrated heterogeneous surfaces characterized by cracks. Among the five formulations, the formulation containing 5.0 g of PVA and 1.5 g of chitosan (F5) exhibited optimal performance, characterized by a thickness of 0.25 mm, a tensile strength of 11.95%, an elongation of 17.83%, and a biodegradation rate of 49.16% after 12 days. The material met JIS Z 1707:1997 standards for mechanical properties, although it did not fully comply with biodegradation requirements. The novelty of this research presents to the valorization of cassava peel starch as local-agro industrial waste into bioplastics enhanced with chitosan and PVA, revealing a cost-effective, renewable alternative that meets key mechanical standards while advancing sustainable plastic innovation. The results indicate that CPS-based bioplastics, when combined with suitable polymer matrices, offer a feasible and sustainable substitute for conventional plastics.